Uma proposta de formação continuada de professores com a temática ambiental por meio de oficinas temáticas - Silveira, Marlise Grecco de Souza (2019)
Considering the relevance of the related thematic with Environmental Education in the school context, this study's objective is to evaluatethe contribution of thematic workshops as a strategy for the continuing education of teachers. Article 1 describes that the public is composed of administrators and classroom teachers. From this standpoint, these teachers were chosen from a prior study with a team derived from three chosen institutions, in which were initially identified the primary environmental problems that plagued them. Thus, it was identified that the worst problem refers to the garbage deposited in the surrounding areas by Uruguaiana's community members, that choose these localized peripheral places to dump objects, and, consequently, they end up attacking the environment. As one of these researched schools is located next to the Uruguai River, one can identify an enormous lack of knowledge in Uruguaiana's community in relation to its natural riches and a lack of concern regarding the city's environmental questions, causing a lack of a critical sense on the students' part in these schools, because, as a majority are unfamiliar with these topics, the students end up reproducing this disinformation even though it is unintentional. Soon, the role of the school will change this thematic by means of an efficient and emancipatory pedagogical intervention for the development of the students' critical thinking. In the manuscript 2, forty teachers from three public schools from the city of Uruguaiana, RS, participated in the study. Inititally, a questionnaire was administered in order to identify the teachers' perception about the environmental thematic. Afterward, the interventions were realized by means of thematic workshops, with this tool being chosen for the environmental education theme. After the interventions, the questionnaire was newly administered to the teachers, in order to identify if there had been changes in these concepts in relation to the proposed subject. As a result, the presented study encountered a significant increase in the teachers' knowledge about the environmental thematic, especially involving the legislation that deals with Environmental Education from Transdisciplinary and Interdisciplinary formats. Based on these findings from the article and manuscripts, we reiterate the importance of using these tools to approach important subjects in the school context. Once, with the collected data from the thematic workshops applied by docents in their respective classrooms, we perceive that teachers seek to share the message of the real importance of knowing Environmental Education, then, from this knowledge the students will be able to know and consequently also will be sensitized relating to the importance of knowing the environmental issues of their community, becoming critical and active subjects in their community and in environmental, political and social discussions relating to their city.